(untitled) (International Journal of Engineering and Computer Science, 2013)
A Software project varies in size depending upon the need. One of the aspect is to manage these projects i.e. Project Management. Various software’s /tools are available for managing the projects. This paper focuses on the comparison between tools for managing the projects based on Agile methodologies namely Scrum and XP(Extreme Programming).